Sexual dimorphism in hemodynamic, cholecystokinetic and microbiome variables in patients with chronic pyelonephritis and cholecystitis an original research article - Kozyavkina, Nataliya V.; Zukow, Walery; Popovych, Andriy I.; Kovalchuk, Halyna Y.; Popovych, Dariya V. (Journal of Education, Health and Sport, 2026)
BACKGROUND. Previous studies on the Truskavets' resort cohort analysed hemodynamic, cholecystokinetic and microbiome variables of patients with chronic pyelonephritis and cholecystitis without stratification by sex, with the sole exception of markedly different testosterone and calcitonin levels. Subsequent work by our group revealed sexual dimorphism in basal electroencephalographic, heart-rate-variability and neuro-endocrine responses to bicycle ergometry, prompting the present retrospective extension of this perspective to the full panel of cardiovascular, biliary and gut-microbiota markers. AIM. To quantify the magnitude and structure of sexual dimorphism across hemodynamic, cholecystokinetic and microbiome variables in patients with chronic pyelonephritis and cholecystitis, to derive a parsimonious discriminant model capable of classifying patient sex with accuracy materially exceeding chance, and to characterise the multivariate relationship between submaximal cardiorespiratory fitness (PWC₁₅₀) and central hemodynamics in both sexes. MATERIALS AND METHODS. Retrospective analysis of a dataset comprising 44 patients (34 men aged 23–70 years; 10 women aged 33–76 years) with verified chronic pyelonephritis and cholecystitis in remission, each tested twice — on admission and after 7–10 days of standard balneotherapy at Truskavets' Spa (drinking of Naftussya bioactive water, ozokerite applications, mineral pools) — yielding 88 observations in total. The following variables were measured: bacteriuria and leukocyturia (quantitative and semi-quantitative Popovych scale); faecal microbiota composition (lactobacilli, bifidobacteria, common and attenuated E. coli, Klebsiella & Proteus); gallbladder cholekinetics by echo-volumogram after xylitol challenge; central and intracardiac hemodynamics by echocardiography (ET, EDV, ESV, SV, CO, GPVR, SCAI, RPCAI); systolic and diastolic blood pressure; Stange's and Guenchi's breath-holding tests; Kerdö autonomic index; and submaximal PWC₁₅₀ on a bicycle ergometer. Raw variables were converted to Z-scores and analysed by forward-stepwise discriminant analysis (Wilks' Λ), multiple regression and canonical correlation using Statistica 6.4 (StatSoft Inc.). RESULTS. Forward-stepwise discriminant analysis selected ten variables — Height, Weight, BP Diastolic, BP Mean, Stange's test, PWC₁₅₀ in W/kg and W, Leukocyturia in lg leukocytes/mL and in Popovych's points, and faecal Bifidobacteria — yielding Wilks' Λ = 0.3815, canonical R = 0.786, χ²(10) = 78, p < 10⁻⁶. The canonical root separated men (centroid −0.68) from women (+2.32); squared Mahalanobis distance D² = 9.0, equivalent univariate effect size d ≈ 3.0; F(10, 8) = 12.5, p < 10⁻⁶. Retrospective sex-classification accuracy reached 95.5% (84/88 correct; 95% Wilson CI: 88.8%–98.5%). Contrary to healthy-population norms, women paradoxically exhibited higher absolute PWC₁₅₀ (164 ± 14 W vs. 147 ± 4 W) and relative PWC₁₅₀ (2.27 ± 0.15 W/kg vs. 1.79 ± 0.05 W/kg; d ≈ 1.6, p < 0.001), alongside more pronounced leukocyturia (d ≈ 0.9, p < 0.01) but comparable bacteriuria (p > 0.10), higher faecal attenuated E. coli and Klebsiella & Proteus, and reduced lactobacilli (all surviving Bonferroni correction, α′ = 0.0125). Multiple regression explained 53.1% of variance in absolute PWC₁₅₀ (R² = 0.531; F(6,81) = 15.3; p < 10⁻⁵; dominant predictor: GPVR, r = 0.52) and 58.3% in relative PWC₁₅₀ (R² = 0.583; F(6,81) = 18.9; p < 10⁻⁵; GPVR r = 0.62), with Sex Index (M=1; W=2) retaining an independent positive contribution (β* = +0.217; p = 0.009). Stange's and Guenchi's breath-holding tests were negligibly correlated with PWC₁₅₀ (|r| ≤ 0.21; equivalence CI ⊂ −0.30, +0.30). CONCLUSIONS. A robust, multisystem sexual dimorphism exists in the integrated hemodynamic, cholekinetic, urinary-inflammatory and gut-microbiota phenotype of patients with chronic pyelonephritis and cholecystitis, captured with 95.5% classification accuracy by ten routinely collected markers and characterised by a "huge" between-sex effect size (D² = 9.0; d ≈ 3.0). Women in this clinical cohort display a more dysbiotic microbiota and a more pronounced urinary-inflammatory profile than men, while paradoxically demonstrating superior cardiorespiratory fitness — a finding contrary to healthy-population norms that warrants prospective confirmation in larger, sex-balanced, multicentre samples. Central hemodynamics, particularly GPVR, are the dominant physiological drivers of PWC₁₅₀, whereas breath-holding tests are not valid proxies of submaximal aerobic capacity in this population.